2022
DOI: 10.1007/s00424-021-02650-y
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ mishandling and mitochondrial dysfunction: a converging road to prediabetic and diabetic cardiomyopathy

Abstract: Diabetic cardiomyopathy is defined as the myocardial dysfunction that suffers patients with diabetes mellitus (DM) in the absence of hypertension and structural heart diseases such as valvular or coronary artery dysfunctions. Since the impact of DM on cardiac function is rather silent and slow, early stages of diabetic cardiomyopathy, known as prediabetes, are poorly recognized, and, on many occasions, cardiac illness is diagnosed only after a severe degree of dysfunction was reached. Therefore, exploration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 311 publications
0
14
0
Order By: Relevance
“…Furthermore, hyperglycaemia itself may promote the development of AGEs (Advanced Glycated End-Products) stimulating collagen expression and accumulation, leading to myocardial fibrosis with an increase in myocardial stiffness and reduced cardiac compliance [ 28 , 33 , 34 , 35 ]. High glucose levels also cause Ca 2+ mishandling and mitochondrial dysfunction, which may play a crucial role in the earliest stages of DCM [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hyperglycaemia itself may promote the development of AGEs (Advanced Glycated End-Products) stimulating collagen expression and accumulation, leading to myocardial fibrosis with an increase in myocardial stiffness and reduced cardiac compliance [ 28 , 33 , 34 , 35 ]. High glucose levels also cause Ca 2+ mishandling and mitochondrial dysfunction, which may play a crucial role in the earliest stages of DCM [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of Ca 2+ homeostasis in mitochondria involves the voltage-dependent anion channel (VDAC), mitochondrial Ca 2+ uniporter complex (MCU), and mitochondrial permeability transition pore (mPTP) ( 184 ). The MCU is a large complex comprising various regulatory proteins, including dominant-negative MCUb, EMRE (essential MCU regulator), and the intermembrane space regulators (EF-hand proteins) MICU1, MICU2, and MICU3.…”
Section: Pathways Regulating Ca 2+ -Dependent Cont...mentioning
confidence: 99%
“…The hypersensitivity of cardiac myofibrils to Ca 2+ is a principal factor which leads to impaired cardiomyocyte relaxation [ 103 ]. Ca 2+ mishandling in DCM results in depressed contractility, slow relaxation, triggered arrhythmias, and altered cellular processes, such as apoptosis or mitophagy [ 104 ]. Studies have shown that green tea catechins can be used for cardiomyopathy patients with diastolic dysfunction because of their desensitizing effects [ 105 ].…”
Section: Attenuation Of Secondary Mitochondrial Diseases By Catechinsmentioning
confidence: 99%